Urgensi Penyelesaian Titik Batas Negara Indonesia dan Timor Leste Melalui Perjanjian Internasional - Bahy Frederick J Eryansan; Stefanus Y Fransisco Kleruk; Yohanes Arman (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to analyze the urgency of resolving the boundary point of Indonesia and Timor Leste through international treaties. This research focuses on the agreements on the state boundary point between Indonesia and Timor Leste that have been agreed upon and how the settlement of state boundary disputes according to international law and what factors make the settlement of the state boundary point between Indonesia and Timor Leste an urgent matter. The research conducted reveals that, before Indonesia and Timor Leste became independent countries, the boundary points had been determined by the Dutch and Portuguese who colonized the island of Timor during the colonial period with the 1904 Dutch-Portuguese convention which later became the basis for agreements to determine the boundary points between Indonesia and Timor Leste when they became independent countries. The settlement of the determination of the boundary point between Indonesia and Timor Leste in the two segments that have not been agreed upon (Noelbesi-Citrana segment and Manusasi-Bidjael Sunan segment) through international treaties is an urgent matter because considering the creation of a clear state boundary point, it can improve bilateral relations between the two countries in various aspects such as in the aspects of economy, tourism, and so on.